Homo-endotaxial one-dimensional Si nanostructures12. Issue 1 (6th December 2017) - Song, Jiaming; Hudak, Bethany M.; Sims, Hunter; Sharma, Yogesh; Ward, T. Zac; Pantelides, Sokrates T.; Lupini, Andrew R.; Snijders, Paul C.
Abstract : Homo-endotaxial 1D Si nanostructure with a higher conductance than the surrounding area. Abstract : One-dimensional (1D) nanostructures are highly sought after, both for their novel electronic properties as well as for their improved functionality. However, due to their nanoscale dimensions, these properties are significantly affected by the environment in which they are embedded. In this paper, we report on the creation of 1D homo-endotaxial Si nanostructures, i.e. 1D Si nanostructures with a lattice structure that is uniquely different from the Si diamond lattice in which they are embedded. We use scanning tunneling microscopy and spectroscopy, scanning transmission electron microscopy, density functional theory, and conductive atomic force microscopy to elucidate their formation and properties. Depending on kinetic constraints during growth, they can be prepared as endotaxial 1D Si nanostructures completely embedded in crystalline Si, or underneath a stripe of amorphous Si containing a large concentration of Bi atoms. These homo-endotaxial 1D Si nanostructures have the potential to be useful components in nanoelectronic devices based on the technologically mature Si platform.